The Relationship of Body Weight, Exclusive Breastfeeding, MP-ASI and Energy Intake with Stunting in Toddlers - Silaban, Verawaty Fitrinelda; Dewi, Lilys Ratna; Sinaga, Lena Murniati; Asmita, Linda; Ginting, Lina Juwanti; Simanjuntak, Linawati (Al-Hijrah Indonesia, 2024)
The incidence of stunting in toddlers is a global nutritional problem. Stunting causes delays in fine motor and gross motor development, increases morbidity and mortality rates, and increases the risk of metabolic disorders in adulthood. The aim of this study was to determine the relationship between body weight, exclusive breastfeeding, MP-ASI (weaning foods) and energy intake with stunting in toddlers aged 24-59 months. This research is descriptive analytical with a cross sectional design. The sample consisted of 92 participants selected using simple random sampling technique. Data collected with body weight measurements for birth weight, exclusive breastfeeding and MP-ASI questionnaires, energy intake calculate using daily energy requirements calculator, and stunting incidence questionnaire. Data analysis was carried out using the Chi-square test (P<0.05). The results of the study explain that there is a relationship between body weight (p=0.000), exclusive breastfeeding (p=0.003), MP-ASI (p=0.004) and energy intake (p=0.000) with the incidence of stunting in toddlers aged 24–59 months. The research conclusion is that there is a relationship between body weight, exclusive breastfeeding, complementary foods and energy intake with the incidence of stunting in toddlers aged 24-59 months.